THEORETICAL AND METHODOLOGICAL ANALYSIS OF PRACTICE TESTS FROM THE SCHOOL COURSE "MAN AND WORLD" (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the methodics of Knowledges tests evaluation in the Humanities and Social cource "Human and the World”, methods of tests classification, psychological and pedagogical conditions, tests objectives and using.
Keywords: 1